2015
DOI: 10.1039/c4cp05917d
|View full text |Cite
|
Sign up to set email alerts
|

Three centered hydrogen bonds of the type CO⋯H(N)⋯X–C in diphenyloxamide derivatives involving halogens and a rotating CF3group: NMR, QTAIM, NCI and NBO studies

Abstract: The existence of three centered C=O···H(N)···X-C hydrogen bonds (H-bonds) involving organic fluorine and other halogens in diphenyloxamide derivatives has been explored by NMR spectroscopy and quantum theoretical studies. The three centered H-bond with the participation of a rotating CF3 group and the F···H-N intramolecular hydrogen bonds, a rare observation of its kind in organofluorine compounds, has been detected. It is also unambiguously established by a number of one and two dimensional NMR experiments, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 44 publications
1
24
0
Order By: Relevance
“…Initial studies were focused on the concentration dependence of NH chemical shift (δ NH ) for all the molecules and it was observed that δ NH remained unaltered for all the molecules, discarding the presence of any type of intermolecular interactions [ 166 ]. Compared to the unsubstituted molecule 33 the chemical shifts of NH protons are observed to be more deshielded for the different substituted molecules, 34 – 38 , indicating the participation of NH proton in weak molecular interactions [ 166 ]. The deshielding of NH chemical shift on lowering the temperature due to the strengthening in the HB is evident from Figure 34 A.…”
Section: Studies On Diphenyloxamidesmentioning
confidence: 99%
“…Initial studies were focused on the concentration dependence of NH chemical shift (δ NH ) for all the molecules and it was observed that δ NH remained unaltered for all the molecules, discarding the presence of any type of intermolecular interactions [ 166 ]. Compared to the unsubstituted molecule 33 the chemical shifts of NH protons are observed to be more deshielded for the different substituted molecules, 34 – 38 , indicating the participation of NH proton in weak molecular interactions [ 166 ]. The deshielding of NH chemical shift on lowering the temperature due to the strengthening in the HB is evident from Figure 34 A.…”
Section: Studies On Diphenyloxamidesmentioning
confidence: 99%
“…45 The phenylacetylene-H 2 O complex has a nearly planar geometry in which both molecules simul- Another comprehensive study on diphenlyoxamide derivatives used NMR spectroscopy, AIM and NCI analyses on intramolecular hydrogen bonds. 46 The structure of diphenyloxamide is shown in Figure 4 and it has the potential for three intramolecular hydrogen bonds. The three 'hydrogen bond angles' for the various derivatives are given in Table 2.…”
Section: Hf Hcl Hbr Hnc Hcn Hcchmentioning
confidence: 99%
“…We found that the NBO analysis did not show any specific overlap corresponding to these BCPs. 51 In the figure 6, sign(2)* is plotted as function 1 on x-axis and its negative values imply attractive interaction (hydrogen bond, halogen bond or van der Waals interaction) whereas positive values imply repulsive interaction (steric effect). This method is able to determine the very weak intramolecular interaction in 1,2-ethanediol which is not identified through BCP.…”
Section: Nci Analysismentioning
confidence: 99%